Month of the Year Effect Pada Beberapa Pasar Modal di Asia Tenggara dan Pasar Komoditas - Robiyanto Robiyanto (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2015)
One of prominent phenomenon in capital market is month of the year effect which is the occurence of certain monthly pattern in capital market return during trading years. There were enormous researches, which had been done to explain this phenomenon in capital market but the results always varied. Unfortunately there was a few research to explain this phenomenon in commodities market. Based on these facts, research about this seasonality still need to be done both in capital market and commodities market. Data used in this study were several South East Asia monthly closing stock market indexes and several commodity product monthly closing prices such as gold, silver, platinum, paladium and West Texas Intermediate Crude Oil during January 1999 – March 2014 period. GARCH (1,1) was employed to analyze the data. The finding shows that month of the year effect still exist in capital market in South East Asia and commodity market during research period with various occurences. Each capital market and commodity market behaves variously during trading year. This may lead to an opportunity, which can be grabbed by active market switching strategy for sophisticated investors, and investors who have multiple access to regional capital markets and commodity markets.